Pengaruh Motivasi, Kepribadian dan Lingkungan terhadap Minat Berwirausaha Masyarakat Gampong Sidodadi Kecamatan Langsa Lama - Suhendra Eka Putra; Abdul Hamid; Mutia Sumarni (JIM: Jurnal Ilmiah Mahasiswa, 2022)
Positive economic growth and the welfare of the people in Indonesia cannot be separated from the efforts of the government and society. One of the efforts made by the community is entrepreneurship, in which the presence of entrepreneurship can help the family economy and participate in the regional economy. The more entrepreneurs, the better the economy. This research was conducted with the aim of knowing the influence of motivation, personality and environment on the entrepreneurial interest of the community in Gampong Sidodadi, Langsa Lama District. This study uses primary data with a sample size of 87 respondents. The data analysis method used is multiple linear regression equation, the coefficient of determination (R2) and hypothesis testing using the t test and F test. The results obtained Y = 0.548 + 0.237X1 + 0.234X2 + 0.265X2. These results indicate that interest in entrepreneurship is 0.548 before being influenced by motivation, personality and environment, while the regression coefficient of motivation, personality and environment has a positive and unidirectional influence on the interest in community entrepreneurship in Gampong Sidodadi. The result of the determination coefficient test is 54.2%, the variables of motivation, personality and environment can explain the variable interest in entrepreneurship. The results of the t test show that motivation is obtained by tcount> ttable (2.622> 1.988) and tsig value <α 5% (0.01 <0.05), personality is obtained by tcount> ttable (2.329> 1.988) and tsig value <α 5% (0.022> 0.05), the environment obtained tcount> ttable (3.690> 1.988) and the tsig value <α 5% (0.000> 0.05) can be stated that partially a significant effect on the interest in community entrepreneurship in Gampong Sidodadi, Langsa Lama District. Likewise the F test, the value of Fcount> Ftable (34.950> 2.71) and the Fsig value <α 5% (0.000 <0.05) it can be stated that motivation, personality and environment simultaneously have a significant effect on the interest in community entrepreneurship in Gampong Sidodadi, Langsa Lama District.